2016
DOI: 10.1111/eva.12429
|View full text |Cite
|
Sign up to set email alerts
|

Geographic extent of introgression in Sebastes mentella and its effect on genetic population structure

Abstract: Genetic population structure is often used to identify management units in exploited species, but the extent of genetic differentiation may be inflated by geographic variation in the level of hybridization between species. We identify the genetic population structure of Sebastes mentella and investigate possible introgression within the genus by analyzing 13 microsatellites in 2,562 redfish specimens sampled throughout the North Atlantic. The data support an historical divergence between the “shallow” and “dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 54 publications
8
41
0
Order By: Relevance
“…Several marine fish species show similar complex patterns of population interaction as the Baltic cod examined in this study (Bekkevold et al, ; Dahle et al, ; Johansen et al, ; Kerr et al, ; Reiss et al, ; Saha et al, ; Wennevik et al, ). As genomic resolution continues to increase in species of interest to fisheries management, it is likely that high powered genetic tools will soon be operational for a range of species.…”
Section: Discussionsupporting
confidence: 61%
“…Several marine fish species show similar complex patterns of population interaction as the Baltic cod examined in this study (Bekkevold et al, ; Dahle et al, ; Johansen et al, ; Kerr et al, ; Reiss et al, ; Saha et al, ; Wennevik et al, ). As genomic resolution continues to increase in species of interest to fisheries management, it is likely that high powered genetic tools will soon be operational for a range of species.…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, neutral loci that we used may not have adequately captured genetic divergence due to local adaptation. Other studies have reported that depth and bottom topography can play important roles in seascape genetics in respect to adaptive divergence using microsatellites (Saha et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, weak currents on spawning sites may restrict the advective transport of eggs and larvae away from the spawning site (Hellberg, ; Palumbi, ) leading to geographic isolation, while oceanic currents may also create isolated circulation cells (White et al, ) and cline formation in species (Knutsen, Jorde, Albert, Hoelzel, & Stenseth, ). Other drivers of genetic structuring in marine populations include local adaptation or selection in response to environmental gradients (Ingram, ; Palumbi, ; Wang et al, ; Waples, ), habitat related ecological factors such as depth, bottom topography (Ingram, ; Prada & Hellberg, ; Saha et al, ) and bottom oxygen concentration (van der Meer et al, ), and also physical discontinuities in basin circulations that limit connectivity (Cadrin et al, ; Knutsen et al, ; Pampoulie et al, ; Stefánsson et al, ). On the other hand, if the currents distribute early life stages over large areas, this can lead to panmixia over broad geographic ranges preventing any genetic structuring (Naro‐Maciel et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Saha et al. () suggested that interspecific introgression might influence allele frequency differences among S . mentella populations in sympatry.…”
Section: Discussionmentioning
confidence: 99%
“…These factors, which may hinder gene flow between populations in Sebastes species, have the potential to promote population differentiation to occur more frequently than in other marine fish (especially pelagic fishes). Conversely, because speciation within Sebastes occurred fairly recently (Briggs, ; Hyde & Vetter, ), much evidence of hybridization has been reported among closely related species due to incomplete or relaxed reproductive barriers in sympatry (Artamonova et al., ; Muto, Kai, Noda, and Nakabo, ; Saha et al., ). This hybridization is a challenge to delimit species and populations.…”
Section: Introductionmentioning
confidence: 99%